PENGARUH KOMPETENSI, TIM KERJA, DAN PENEMPATAN TERHADAP KINERJA PERSONEL BADAN PENELITIAN DAN PENGEMBANGAN KEMENTERIAN PERTAHANAN - Tur Adhi Handono; Sri Widodo (Inovasi, 2022)
This study aims to prove the effect of competence, team work, and placement on the performance of the Ministry of Defense Research and Development Agency personnel. This study uses a quantitative approach, survey methods and path analysis. The population is 72 employees. Using simple random sampling technique, 61 respondents were obtained. Data were analyzed using SPSS 25.00 software. The results of the study show that: Competence has a positive and significant direct effect on placement of 62.2%; The work team has a positive and significant direct effect on placement by 34%; Competence has a positive and significant direct effect on performance by 25.5%; The work team has a positive and significant direct effect on performance by 15.9%; Placement has a positive and significant direct effect on the performance of the Ministry of Defense Research and Development Agency personnel by 60.4%. The implication is that to improve the performance of the Ministry of Defense Research and Development Agency personnel, it is necessary to improve the quality of competence, the solidity of the work team, and the accuracy of the requirements for placement.Keywords: Competencies, Work Teams, Placements, Performance